Clinical profiles of stigma experiences, self-esteem and social relationships among people with schizophrenia, depressive, and bipolar disorders. Issue 1 (30th September 2015) - Oliveira, Sandra E.H.; Esteves, Francisco; Carvalho, Helena
Abstract: Some mental illnesses and certain mental health care environments can be severely stigmatizing, which seems to be related to decreased self-esteem and a deterioration of the quality of social relationships for people with mental illness. This study aims to identify clinical profiles characterized by clinical diagnoses more strongly associated with the treatment settings and related to internalized stigma, self-esteem and satisfaction with social relationships. It also aimed to analyze associations between clinical profiles and socio-demographic indicators. Multiple correspondence analysis and cluster analysis were performed on a sample of 261 individuals with schizophrenia and mood disorders, from hospital-based and community-based facilities. MCA showed four distinct clinical profiles allowing a differentiation among levels of: internalized stigma, social relationship satisfaction and self-esteem. Overall, results revealed that internalized stigma remains a pervasive problem for some people with schizophrenia and mood disorders. Particularly, internalized stigma and social relationships dissatisfaction and associated socio-demographic indicators appear to be a risk factor for social isolation for individuals with schizophrenia, which may worsen the course of the disorder. Our findings highlight the importance to develop structured interventions aimed to reduce internalized stigma, and exclusion of those who suffer the loss of their social roles and networks. Highlights: Distinct clinical profiles (CP) were identified among mental health consumers. CP discriminated among self-stigma; social relationships satisfaction; self-esteem. CP were associated with different treatment settings and socio-demographic indicators. Self-stigma: risk factor for isolation in schizophrenia, regardless treatment setting. CP: a clear picture for interventions to battle self-stigma and social exclusion.